2019
DOI: 10.21203/rs.2.14859/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors of anemia among Women of Reproductive Age in Rwanda: implications for designing better interventions

Abstract: Background Anemia among Women of Reproductive Age (WRA) continues to be among the major public health problems in many developing Rwanda where It was increased comparing 2015 to 2010 Demographic and Health Survey (DHS) reports. A thorough understanding of the its risk factors is necessary to design new better approaches. However, to the best of our knowledge, no study assessing factors associated with anemia among WRA has been conducted. Therefore, this study aims to identify anemia risk factors among WRA in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Varied results were found in studies conducted in Bangladesh 19 and Rwanda. 20 The study in Bangladesh reported that women with low education, working and living in rural areas are more likely to have anemia. 19 Different results were found in Rwanda where there was no relationship between education and anemia but widows were more likely to have anemia.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Varied results were found in studies conducted in Bangladesh 19 and Rwanda. 20 The study in Bangladesh reported that women with low education, working and living in rural areas are more likely to have anemia. 19 Different results were found in Rwanda where there was no relationship between education and anemia but widows were more likely to have anemia.…”
Section: Original Articlementioning
confidence: 99%
“…19 Different results were found in Rwanda where there was no relationship between education and anemia but widows were more likely to have anemia. 20 Research in Myanmar 21 found that high parity is more likely to be connected with anemia.…”
Section: Original Articlementioning
confidence: 99%
“…More than 100 million African children are thought to be anaemic and community-based estimates of anemia prevalence in children in settings where malaria is endemic range between 49% and 76% [19] but there is no documentation on the prevalence of anemia among female University students in African settings. In East Africa, anemia continues to be a serious public health problem, the prevalence of anemia in women of reproductive age such as female university students is higher, which ranges from 19.2% in Rwanda to 49% [20,21]. A recent study in Mwanza, Tanzania reported a prevalence rate of anemia at 77.2% [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Rwanda have focused on women of reproductive age in general [27][28][29][30][31], with only one study focusing on anaemia among pregnant women [32]. Moreover, this was a hospital-based study, and therefore not representative of all pregnant women in Rwanda [32].…”
Section: Introductionmentioning
confidence: 99%